Behavioral and electrophysiological effects of endocannabinoid and dopaminergic systems on salient stimuli - Laricchiuta, Daniela; Musella, Alessandra; Rossi, Silvia; Centonze, Diego (Frontiers in Behavioral Neuroscience, 2014)
Rewarding effects have been related to enhanced dopamine (DA) release in corticolimbic and basal ganglia structures. The DAergic and endocannabinoid interaction in the responses to reward is described. This study investigated the link between endocannabinoid and DAergic transmission in the processes that are related to response to two types of reward, palatable food and novelty. Mice treated with drugs acting on endocannabinoid system (ECS) (URB597, AM251) or DAergic system (haloperidol) were submitted to approach-avoidance conflict tasks with palatable food or novelty. In the same mice, the cannabinoid type-1 (CB1)-mediated GABAergic transmission in medium spiny neurons of the dorsomedial striatum was analyzed. The endocannabinoid potentiation by URB597 magnified approach behavior for reward (food and novelty) and in parallel inhibited dorsostriatal GABAergic neurotransmission. The decreased activity of CB1 receptor by AM251 (alone or with URB597) or of DAergic D2 receptor by haloperidol had inhibitory effects toward the reward and did not permit the inhibition of dorsostriatal GABAergic transmission. When haloperidol was coadministered with URB597, a restoration effect on reward and reward-dependent motor activity was observed, only if the reward was the palatable food. In parallel, the coadministration led to restoring inhibition of CB1-mediated GABAergic transmission. Thus, in the presence of simultaneous ECS activation and inhibition of DAergic system the response to reward appears to be a stimulus-dependent manner.